2013
DOI: 10.1111/cdev.12136
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Induced Elevation of Oxytocin in Maltreated Children: Evolution, Neurodevelopment, and Social Behavior

Abstract: Child maltreatment often has a negative impact on the development of social behavior and health. The biobehavioral mechanisms through which these adverse outcomes emerge, however, are unclear. To better understand the ways in which early life adversity affect subsequent social behavior, changes in the neuropeptide oxytocin in children (n=73) aged 8.1–11.5 years following a laboratory stressor were examined. Girls with histories of physical abuse have higher levels of urinary oxytocin and lower levels of saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 80 publications
(89 reference statements)
7
78
2
Order By: Relevance
“…Recent work has shown that some subjects having experienced childhood abuse exhibit lower levels of cortisol, with marked differences depending on gender (7982), time of cortisol sampling (79), source tissue (83), type of abuse (84, 85), and the presence of concurrent psychiatric (71, 78) or other health conditions (84). Importantly, decreased cortisol may not be exclusively linked to PTSD (83, 86), as has often been supposed (87, 88); rather, decreased cortisol production may reflect an adaptation to chronically stressful situations, whereas elevated cortisol production may prime individuals to react to unpredictable stressors, and these situations may both constitute ELA (81). Currently, it is difficult to draw conclusions on the overall impact of GR methylation variations on basal and reactive cortisol levels, as the majority of studies investigating GR promoter methylation did not measure cortisol levels.…”
Section: Resultsmentioning
confidence: 94%
“…Recent work has shown that some subjects having experienced childhood abuse exhibit lower levels of cortisol, with marked differences depending on gender (7982), time of cortisol sampling (79), source tissue (83), type of abuse (84, 85), and the presence of concurrent psychiatric (71, 78) or other health conditions (84). Importantly, decreased cortisol may not be exclusively linked to PTSD (83, 86), as has often been supposed (87, 88); rather, decreased cortisol production may reflect an adaptation to chronically stressful situations, whereas elevated cortisol production may prime individuals to react to unpredictable stressors, and these situations may both constitute ELA (81). Currently, it is difficult to draw conclusions on the overall impact of GR methylation variations on basal and reactive cortisol levels, as the majority of studies investigating GR promoter methylation did not measure cortisol levels.…”
Section: Resultsmentioning
confidence: 94%
“…For example, inOT increased the probability of aggression among high trait aggression people towards an intimate partner, as self-disclosed by participants, following a provocation task (16), and that OT increases anxiety to unpredictable threat (56). Moreover, contrary to what would be predicted by the OT stress theory, it has been reported that offenders who experienced early childhood maltreatment show raised urinary OT levels (a putative measure of OT) (57,58) (However, see Heim et al for contradictory findings (59)). Similarly, plasma OT levels correlated with higher social anxiety symptoms in patients with Generalized Social Anxiety Disorder (60), as well as with interpersonal distress (17).…”
Section: Oxytocin Stress and Social Saliencementioning
confidence: 99%
“…The attenuation of the cortisol response to a stressful event parallels the finding by Trickett et al (2010) of lower morning cortisol concentrations in child victims of sexual abuse. More importantly, Seltzer et al (2013) have also recently demonstrated that physically maltreated girls have a dampened cortisol response following a social stressor. In particular, our study shows that it is the children residing in a children's home who present with an apparent lack of an appropriate HPA response when faced with a further stressor, which in this study was the forensic examination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the information that the clinic was given by the caregivers of the home was that the mothers of these children were deceased and that they were found living as street children in an unsavory part of Johannesburg. Thus, the attenuated stress response may not be due to the children's home per se, but rather the additional stressors and traumas, such as the loss of primary attachment figures, that these children have experienced (Seltzer et al 2013). Utilizing a laboratory social stressor with groups of adolescents, Ayer et al (2013) have recently shown that blunted salivary cortisol responses following a stressor are associated with persistent behavioral dysregulation.…”
Section: Discussionmentioning
confidence: 99%